PENGARUH MODAL DAN TENAGA KERJA TERHADAP PENDAPATAN PELAKU USAHA GENTENG DI DUSUN SARIP, DESA KARANGASEM, KECAMATAN WIROSARI,KABUPATEN GROBOGAN - Fidyah Yuli Ernawati; Cahyani Tunggal Sari; Mei Dina Anggita Widyawati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
As an industrial center area, Wirosari sub-district has the opportunity to develop a better tile industry, so that it will affect income levels. This study aims to determine the effect of capital and labor variables on the income of roof tile business actors, Sarip Hamlet, Karangasem Village, Wirosari District, Grobogan Regency. The method used in this research is quantitative method. The total population in this study was 1,100 tile business actors. Determination of the sample in this study used the simple random sampling method, which means that each population is given equal rights and is randomly selected to be sampled. The sample in this study were 92 respondents with the calculation of the number of samples using the Slovin formula. The results of the multiple regression analysis equation from this study are known as follows: Y = 4.553 + 0.329X1 + 0.490X2 + e. The results of the data analysis carried out, the indicators used in this study are all valid and reliable. For the results of the classical assumption test, all data are normally distributed. The results of the t test show that capital has a partial or separate effect on the income of roof tile business actors in Karangasem village, Wirosari sub-district, Grobogan district with a t count (3.276) > t table (1.987) and a significant value of 0.001 <0.05. The results of the t test show that labor has a partial or separate effect on the income of tile business actors in Sarip Hamlet, Karangasem Village, Wirosari District, Grobogan Regency with a t count (4.426) > t table (1.987) and a significance of 0.000 <0.05. The results of the F test in this study indicate that capital and labor have a proper effect on the income of roof tile business actors in Karangasem village, Wirosari sub-district, Grobogan district with an F count (15.038) > F table (3.099) and a significance of 0.000 <0.05. The test results for the coefficient of determination in this study were 0.253, which means that the independent variables (capital and labor) have an influence on the dependent variable (income) of 25.3%. Tile business actors are advised to strengthen and increase capital for business development and maintain business continuity. There needs to be an effort to increase capital by setting aside some of the remaining business results. This is done so that the business can develop properly. Not only capital, but labor needs to be considered by tile business actors by maintaining the existing workforce and adding workers so that tile production increases and can increase sales and income